Remarks on some historical-cultural developments in the Armenian Highland during the late bronze – early iron ages - Tumanyan, Garegin (History and Culture, 2025)
Formed in Northern Mesopotamia and southern Armenian Highland, Mittani kingdom occupied enormous territory, named "Fertile Crescent" in historiography. In the war against Assyria under Shalmaneser I, Mittani and its allies suffered heavy defeat, yet, continued struggling against Assyria’s expansionist ambitions. Armenian Highland’s provinces Harq (Turuberan region) and Aragatsotn (Ayrarat region) became powerful centers of resistance. Probably, this was the consequence of migration of population groups intolerant to Assyrian domination to the north. This is evidenced by archaeological data and toponymical parallels, also, data preserved in Armenian historians’ works drawn from "Hayk and Bel" legend. Inscriptions of Tukulti-Ninurta I state that the rebellious country of Kadmukhi was occupied and a tribute imposed on it. There are parallels of some Mittani toponyms in Armenian Highland. Possibly, during the discussed period, the population of Mittani migrated in two directions – to the north-west and north-east. The cultural ties between people of Mittani and Armenian Highland covered various spheres: writing, military affairs, glyptics, metalworking, pottery, etc. Some traditions of Mittani were preserved in Armenian Highland and successfully developed later-on. Iron Age culture of Armenian Highland, immediately preceding the ancient Armenian culture (from late period to early phase, inclusive), could be named “most ancient Armenian culture”.